MicroRNA-96 plays an oncogenic role by targeting FOXO1 and regulating AKT/FOXO1/Bim pathway in papillary thyroid carcinoma cells - Song, Hong-Ming (Int J Clin Exp Pathol, 2015)
MicroRNAs (miRNAs) are kind of small non-coding RNAs that negatively regulate gene expression at post-transcription level, and those non-coding RNAs appear to play a key role in tumorigenesis. The aim of this study was to investigate the biological role of miR-96 in papillary thyroid carcinoma (PTC) cell lines. We identified miR-96 to be up-regulated in PTC specimens in comparison to matched normal tissues by microRNA microarray and RT-qPCR analysis (P < 0.05). Next, to explore the potential function of miR-96, PTC cell lines K1 and TPC1 were transiently transfected with miR-96 mimics and inhibitor. Successful transfection being confirmed by RT-qPCR. Ectopic expression of miR-96 promoted proliferation and colony formation ability, and inhibited apoptosis of K1 and TPC1 cells, whereas down-regulated expression of miR-96 suppressed those functions when compared with the control cells. According to a computational prediction, FOXO1 maybe a potential target of miR-96. Luciferase assays revealed that miR-96 is directly targeted to both binding sites of FOXO1 3’-untranslated region (3’-UTR) and suppressed the FOXO1 expression, and subsequently inhibited the expression of Bim protein in PTC cells. Moreover, the expression of FOXO1 had an inverse correlation with expression of miR-96 in PTC specimens by RT-qPCR and western blot analysis. The data from the present study demonstrated that miR-96 can promote proliferation, and inhibit apoptosis in PTC cell lines K1 and TPC1, thus miR-96 may play an oncogenic role in PTC by inhibiting the FOXO1 and regulating AKT/FOXO1/Bim pathway, and it may serve as a novel therapeutic target for miRNA-based PTC therapy.